ORDERING SYSTEM ITEMS AT U.D BHAKTI PUTRA PANDAWA - Ratnaningsih Ratnaningsih; Jalinas Jalinas Skom., MMSI (Jurnal Sistem Informasi, 2003)
U.D BHAKTI PUTRA PANDAWA is a company which is engaged in the minimum distribution. but in ordering goods entering the system, there is still lack of delivery of ordered goods data information and data items have been received by the company. this is because the process is done manually. therefore, the author of this fix these deficiencies in the form of research writing under the title "Draft Articles on the reservation system U.D Bhakti Putra Pandavas". in this system writer using microsoft visal Basic 6.0. By using computerized in this system, has advantages such as speed of obtaining information, data storage, process calculations as well as making statements in accordance with company expectations.